Needs Analysis: Implementation of Outdoor STEM Learning in Biology Education at High School - Madani, Willy Faisal; Auliya, Roudhatul; Nadillah, Sabrina; Sari, Indah Juwita; Alasa, Victor; Triplett, Angela; Triplett, William J. (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study examined the preparation and implementation of outdoor learning by integrating STEM concepts into Biology Education. It highlights the opportunity for further investigation into how the STEM approach can enrich students’ learning experiences in outdoor learning. The research uses a case study method with a qualitative approach, where data is collected through observations and interviews to understand the implementation of Outdoor STEM Learning in Biology Education at high schools. Data collection was conducted at two schools, with two Biology teachers as informants from one high school in Banten and Jakarta. The findings reveal that both schools have not yet implemented the Outdoor STEM Learning concept in Biology Education. However, both show a growing interest and curiosity to adopt it, especially with the implementation of the Merdeka Curriculum. Challenges such as limited resources, facilities, and teacher training pose obstacles, but it is hoped that this implementation could enhance learning experiences, strengthen the understanding of Biology, and develop students’ character.